Seroprevalence of coxsackievirus A16 antibody among people of various age groups: a systematic review and meta-analysis - Peng Li; Yan Chen; An Tang; Fan Gao; Jian-Bo Yan (BMC, 2021)
Abstract Background Coxsackie virus group A type 16 (CoxA16) is the main pathogen and usually an alternative to or joins in prevalence with enterovirus 71 (EV71) causing hand, foot and mouth disease (HFMD). The objective of this study was to estimate the seroprevalence of CoxA16 antibody among people of various age groups by a systematic review and meta-analysis. Methods The literature of seroprevalence of CoxA16 antibody among people has been systematically searched through databases from the date of their establishment to Jan. 2021. Estimates of seroprevalence of CoxA16 antibody by gender and age groups have been summarized by using fixed- and random- effect models. All analyses have been conducted in STATA version 12.0 software. Results A total of 14 publications with 9 in English and 5 in Chinese containing 9562 samples were finally included in the meta-analysis. The seroprevalence of CoxA16 antibody reported in different studies range from 24.85 to 76.92 %. Meta-analysis has revealed that the seroprevalence of CoxA16 antibody was 56.3 % (95 %CI: 47.7 %~64.9 %) in the overall population and 55.1 % (95 %CI: 44.1 %~66.1 %) in the Chinese population. Subgroup analysis by gender has revealed that the seroprevalence of CoxA16 antibody was 56.1 % (95 %CI: 45.2 %~67.1 %) in males and 60.0 % (95 %CI: 50.0 %~69.9 %) in females. Subgroup analysis by age groups has revealed that the seroprevalence of CoxA16 antibody was 49.1 % (95 %CI: 36.2 %~62.0 %) in the 0 ~ 5 age group and 63.9 % (95 %CI: 53.1 %~74.7 %) in the over 5 age group. Begg's funnel plots have suggested that there were no publication bias in all groups. Sensitive analysis has suggested that the result of the meta-analysis was stable. Conclusions The seroprevalence of CoxA16 antibody was closely related to age. Children under 5 years old were the main susceptible groups for CoxA16 and also the key groups for the prevention and control of HFMD.